SOCIO-CULTURAL CONSTRUCTION OF SPACE AS A FACTOR TO MAKE A REGION MORE ATTRACTIVE FOR TOURISTS - Kleimenov, Sergey; Kleimenova, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This study aims at the analysis of the current situation in the tourist industry of Pskov region, its economic efficiency and means of making the area more interesting for holidaymakers. The research problem is the low tourist flow in the area and the low economic efficiency of the industry. The tourist companies which promote Pskov region can be described as conservative and rigid. They offer visiting traditional tourist attractions such as churches, monasteries, and estates of famous historic persons. The key results are the following. Mythological and fictional characters can be successfully used as attractors. Nowadays, British tour operators offer three types of “fictional” tours. Firstly, tours devoted exclusively to locations described in myths and fiction. Secondly, tours that combine traditional and fictional sights. Thirdly, visiting places for which local myths and legends were intentionally coined. The authors suggest that tours of the third type should be actively used to boost the popularity of Pskov region. Thus, modern mythopoeia is regarded not only as a creative activity but also as an economic instrument of constructing a new socio-cultural space. The results of the study are based on the careful examination of statistic data and the analysis of texts on British sights. The list of primary methods include analogy approach, description, hypothetico-deductive and axiomatic methods.